Free Time Activities in Scholars - Supelano-Cuervo, David-Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This review article presents the positions of different authors regarding the conceptualization of leisure and free time, added to the activities to measure the use of this time in young people. Its objective is to collect and analyze research where each author expresses his position in the definitions of leisure and free time and the activities in this time, considering the benefits depending on the value judgment of each one. A documentary review of articles research results of the last 20 years is carried out, in the Dialnet, Scielo, Redalyc, EBSCO, Research Gate databases; about the concept and the activities of measurement of the use of Leisure and Free Time (OTL) in young people, in addition, how they are expressed and shown in other populations in order to recognize the influence of these activities on them, where the following were used Keywords: leisure, free time, young people, leisure activities and free time. It is concluded that there is a lot of variety in terms of positions regarding the concept of leisure free time; each author expresses his point of view adding his value judgment in each of his assessments on this topic. There is no tendency to practice a certain activity, but the options for practicing activities for young people are varied. This review allows us to give a broader view of these terms, not only conceptually but also on a personal level, added to the benefits that this time brings and its importance on a day-to-day basis.